Peer teaching: a solution to overcome the imbalance of psychomotor performance and social interaction in physical education learning - Asngari, Asngari; Sumaryanto, Sumaryanto (Universitas Nusantara PGRI Kediri, 2019)
The learning process through peer teaching model is the teaching strategy used in physical education. Through interaction with peers or across the same age, the learning could occur in various domains. Physical education learning with various students characteristics results in the ability in absorbing the learning material as well. It causes the imbalance of psychomotor performance and social interaction. States that physical education in it also contains several demands change in the cognitive, affective, and psychomotor domains at the individual micro level. The purpose of the critical literature review of the writer is to find out that peer teaching is as a solution to overcome the imbalance of psychomotor performance and social interaction in physical education learning. This review contains a collection of international journals dealing with the topic of discussion collected and reviewed in this article. There are 10 international journals appropriate for the topic. The main finding of this review is that peer teaching is one of learning models which could be used to overcome the imbalance of psychomotor performance and social interaction. Peer teaching concept that has been compiled by Metzler using peer assistance contributes to the implementation of physical education learning. The students’ psychomotor performances which have not been evenly distributed could be helped by peer likewise social interaction.